2016
DOI: 10.1016/j.bbadis.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload inhibits osteogenic commitment and differentiation of mesenchymal stem cells via the induction of ferritin

Abstract: Osteogenic differentiation of multipotent mesenchymal stem cells (MSCs) plays a crucial role in bone remodeling. Numerous studies have described the deleterious effect of iron overload on bone density and microarchitecture. Excess iron decreases osteoblast activity, leading to impaired extracellular matrix (ECM) mineralization. Additionally, iron overload facilitates osteoclast differentiation and bone resorption. These processes contribute to iron overload-associated bone loss. In this study we investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 51 publications
6
92
0
1
Order By: Relevance
“…Other in vitro studies on human osteoblasts suggested that the ferroxidase activity of ferritin that inhibits the mineralization and downregulates the alkaline phosphate expression and activity [39], both, could be explanations for low cortical BMD. Iron selectively inhibits differentiation of multipotent mesenchymal stem cells to osteoblasts [40]. This is in line with studies on HHC patients, a negative impact of hepatic iron concentrations on BMD, [10] and an association of osteoporosis with the severity of iron overload at diagnosis (reflected by serum ferritin levels or iron removed to reach depletion), but transferrin saturation was not determined [11,20].…”
Section: Pathophysiological Explanatory Approachessupporting
confidence: 78%
“…Other in vitro studies on human osteoblasts suggested that the ferroxidase activity of ferritin that inhibits the mineralization and downregulates the alkaline phosphate expression and activity [39], both, could be explanations for low cortical BMD. Iron selectively inhibits differentiation of multipotent mesenchymal stem cells to osteoblasts [40]. This is in line with studies on HHC patients, a negative impact of hepatic iron concentrations on BMD, [10] and an association of osteoporosis with the severity of iron overload at diagnosis (reflected by serum ferritin levels or iron removed to reach depletion), but transferrin saturation was not determined [11,20].…”
Section: Pathophysiological Explanatory Approachessupporting
confidence: 78%
“…In vivo experiments in mice were able to reproduce these findings. The inhibitory effect of iron, however, was specific for osteogenic lineage differentiation, whereas no impact on chondrogenesis and adipogenesis was noted [163].…”
Section: Iron (Fe 2+ )mentioning
confidence: 92%
“…Iron overload in mice results in increased bone resorption and oxidative stress, leading to changes in bone microarchitecture and bone loss. Iron can directly inhibit osteogenic commitment and bone marrow stromal cell differentiation [ 92 ]; however, the underlying mechanism remains unknown.…”
Section: Molecular Mechanism Of Bone Remodeling and Osteoporosismentioning
confidence: 99%